Cycling Reduces Pollution and Tracing Tai Lue Culture on Both Sides of Mekong River - Jeenpracha, Panadda; Peltier, Anatole-Roger (Academic Journal of Thailand National Sports University, 2022)
The guideline to develop tourism for enhancing Thai Tourism competition is that the development of Thai Tourism quality to increase the employment and income providing to communities. Mentioned on community participation and develop new service sections to get along with local potentiality such as ways of life, natural environment, art and culture and local traditions. In addition, Thai Industry tourism should promote domestic tourism and cooperate with neighborhood countries like GMS countries (Greater Mekong Sub-region) and aim to be the Tourism Capital of Asia and Quality Tourism Destination. For instance, cycling can access to tourist attractions is one of tourism model to get along well with the environment changes that are saving energy and to be synchronized with the conservation of local culture and local tradition such as Tai Lue, Shan and many ethnic groups who have outstanding history and reflected Thai origins as well.